Amplatzer occluders – a breakthrough in the interventional treatment of congenital heart defects. 27 years of experience - Białkowski, Jacek; Szkutnik, Małgorzata (Pediatria Polska - Polish Journal of Paediatrics, 2025)
This review synthesizes the experience of a single institution in the percutaneous closure of the most common congenital heart defects – atrial septal defect (ASD), ventricular septal defect (VSD), and patent ductus arteriosus (PDA) – using Amplatzer devices. For ASD, more than 2,000 procedures have been performed. Special attention is given to the age limits for this procedure. In the case of small PDAs, a documented shift in strategy from coils to the new Amplatzer Duct Occluder II Additional Sizes has occurred. The Amplatzer Duct Occluder type I remains the best device for closing larger PDAs (diameter > 2.5 mm). The most challenging percutaneous procedures remain VSD closures. Muscular VSDs (though less frequent) are likely the preferred candidates for this method, whereas perimembranous VSD closures remain a controversial issue. The article also describes an educational program for training foreign interventional cardiologists. In conclusion, the introduction of Amplatzer occluders into clinical practice represents a true breakthrough in the treatment of selected congenital heart defects.